Negotiating Social Class Through Language Style In Charles Dickens' Great Expectations: A Sociolinguistic Analysis - Kamaluddin, Mohamad Ihsan; Deni Suswanto; Erlan Aditya Ardiansyah (Journal of Authentic Research, 2026)
Language plays a vital role in reflecting and shaping social class within society. This study explores how social class is represented through language in three literary works—Charles Dickens' Great Expectations, Charles Dickens' Oliver Twist, and George Bernard Shaw's Pygmalion—using Pierre Bourdieu's ideas of linguistic capital, symbolic power, and social distinction. The research aims to understand how language acts as a social resource involved in constructing, negotiating, and maintaining social hierarchies in these texts. Using a descriptive qualitative method, data were gathered through purposive sampling and detailed reading, yielding 24 quotations for analysis. These were interpreted within Bourdieu's sociological framework and examined through qualitative content analysis. Results show that linguistic capital is depicted through characters' efforts to adopt socially valued language for upward mobility; symbolic power appears in the authority of individuals and institutions to legitimize certain linguistic forms; and social distinction is prominent as language helps enforce class boundaries and social differences. Overall, the study concludes that language is more than a communication tool—it is a mechanism that influences how social class is negotiated, sustained, and reproduced. These insights highlight Bourdieu's theory as a useful lens for understanding the link between language and social inequality in literary works.